INDIKASI ENDAPAN TSUNAMI BERDASARKAN SUBFOSIL DI RAWA DAERAH SIMEULUE, SUMATERA UTARA - Lestari, Raihanna Ayu; Fauzielly, Lili; -, Winantris; -, Yudhicara (Bulletin of Scientific Contribution, 2014)
Administratively, the study site is located in Sumatra Utara region, on swamp area at Simeuleu Island, which has coordinates point on 95° 43’ 15” BT and-2° 45’ 29” LS. Subfossil group used are foraminifera and ostracoda. Based on Simeuleu core analysis of lithological and biofacies, the study area are divided into 3(three) biofacies namely A,B and C. in Biofacies A, Heterolepa subhaidingeri is found as the predominate species that live in outer neritic environment. In Biofacies B, Elphidium depressulum is found as the predominate species that live in middle neritic environment. And in Biofacies C, Hanzawaia grossepuncata and Pararotalia calcariformata are found as the predominate species that live in middle neritic environment. Origin of depositional environment of tsunami deposits is middle neritic and outer neritic.